The Extraterritorial Effects of Sanctions - Ohyun Kwon; Constantinos Syropoulos; Yoto V. Yotov; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
We provide quantitative evidence that the primary effects of economic sanctions on trade and welfare are accompanied by strong extraterritorial effects — estimates of the former effects may be significantly biased if the latter effects are not taken into account. Furthermore, while the extraterritorial burden of sanctions on trade falls primarily on target countries, the corresponding effect on trade among senders and third countries is positive. General equilibrium analysis suggests that, for targets, the welfare losses due to extraterritorial effects are large and may exceed the losses due to reduced trade with senders. For senders, the gains from increased trade with third countries may outweigh the losses from decreased trade with targets to generate net welfare gains. The welfare effects on third countries are significant, too. However, the direction and size of these effects depend on three key factors: the size of the target, the size of the sender, and the economic ties among the target, the sender, and third countries.
Keywords: F14; F51; Q17; 330; economic sanctions; primary effects; extraterritorial effects; trade; welfare